A novel colorimetric assay based on the peroxidase-like properties of amino functionalized copper metal–organic framework nanoparticles for ascorbic acid sensing. Issue 12 (6th March 2019) - Yao, Zhixia; Li, Zhen; Liu, Hanmeng; Liu, Yaosheng; Sun, Yujing; Li, Zhuang
Abstract : A novel sensing system using Cu-BDC-NH2 provides an effective strategy for AA detection with a lower LOD than that of many conventional methods. Abstract : A rapid and sensitive colorimetric strategy for the determination of ascorbic acid (AA) is presented, using amino functionalized copper metal–organic framework nanoparticles (Cu-BDC-NH2 NPs) with effective intrinsic peroxidase-like properties. In our design, Cu-BDC-NH2 NPs catalyze the H2 O2 oxidation of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) generating blue-colored oxidized TMB (ox-TMB) with a significant absorbance at 655 nm in the UV-vis spectrum. AA can reduce ox-TMB, inducing a dramatic blue color fading and a decrease in absorbance. Under the optimal experimental conditions, this proposed system presents a good linear relationship (0.5–60 μM) and the detection limit is 0.15 μM. Repeatability, high selectivity and practicability are also well-studied, proving that the sensing system based on Cu-BDC-NH2 NPs can be successfully applied for colorimetric detection of AA in human serum, food and pharmaceutical samples. The designed method can provide a highly selective and sensitive optical sensing system to detect AA and establish a new platform to develop extensive applications of metal–organic framework nanoparticles with enzyme-mimetic activity in colorimetric biosensing.